1989
DOI: 10.1159/000185375
|View full text |Cite
|
Sign up to set email alerts
|

Triamterene and the Kidney

Abstract: Triamterene (TA) is a mild ‘potassium-sparing’ diuretic usually employed in combination with other more potent diuretics in the treatment of hypertension. TA pharmacokinetics and pharmacodynamics in normal volunteers, elderly subjects and in patients with renal and hepatic dysfunction are reviewed. A variety of adverse renal effects, such as abnormalities in urinary sediment, nephrolithiasis, interstitial nephritis and acute renal failure, has been reported to occur and is also reviewed. Of particular concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 32 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…4 Urine sediment abnormalities occur in up to 54% of patients. 5, 6 Fairley et al 7 found triamterene crystals and casts in acidic urine in all 20 healthy individuals 2-11 hours after receiving a single 100-mg dose of triamterene.…”
Section: Discussionmentioning
confidence: 99%
“…4 Urine sediment abnormalities occur in up to 54% of patients. 5, 6 Fairley et al 7 found triamterene crystals and casts in acidic urine in all 20 healthy individuals 2-11 hours after receiving a single 100-mg dose of triamterene.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its weak BP-lowering properties, triamterene is seldom employed as monotherapy for hypertension. It is usually used in combination with a thiazide-type diuretic with the premise behind such a two-diuretic combination being that triamterene reduces the K + and Mg ++ losses that might otherwise accompany thiazide therapy [ 48 ]. Triamterene, given together with a NSAID, has been reported to cause acute kidney injury, which may last for several days.…”
Section: Triamterenementioning
confidence: 99%
“…Subsequent studies in the 1980s and early 1990s demonstrated that triamterene was a frequent nephrolithiasis culprit, accounting for up to onethird of drug-induced stone cases [3,7,[26][27][28]. Many patients had prior history of calcium or uric acid calculi, suggesting a mechanistic role of heterogeneous nucleation or accretion of triamterene onto prior stones [3,5,[26][27][28]. However, the last 15 years have seen a decline in the incidence of triamterene-related stones due to growing physician awareness and alternative hypertensive agents.…”
Section: Triamterenementioning
confidence: 99%
“…Daily doses of triamterene exceeding 150 mg are usually required for stone formation [3]. In addition, alkaline pH increases tubular reabsorption of triamterene, leading to a decrease in both crystalluria and calculi formation [28,33].…”
Section: Triamterenementioning
confidence: 99%